DIDACTIC FOUNDATIONS OF COGNITIVE ACTIVITY AND ITS DEVELOPMENT IN STUDENTS - Ahmedova Mastura Mahmudovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article focuses on the nature of the cognitive process, the levels of the cognitive process, methods, means, types of training, the issues of enhancing the cognitive activity of students and improving the effectiveness of training.